Love's long journey - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House Publishers, 2003)
After all their dreaming and planning, Missie and her beloved Willie are actually on the trail west in a covered wagon, leaving behind her also-beloved family. Her memories are bittersweet as she faces the hardships of the westward trek--the rain, the mud, the impassable rivers, and even death. Will their love for each other and faith in God survive the bewildering surprise at journey's end?
The Journey Begins -- Day's End -- Another Day -- Traveling Neighbors -- Rebecca Clay -- Tedious Journey -- Rain -- The Big River -- Town -- Breaking Camp -- A Tough Decision -- The Taylorsons -- News -- Sunday -- Surprises -- The Ranch -- Winter and Christmas -- Missie's New Home -- Missie's Garden -- Summer -- Willie's Return -- Afternoon Tea -- Another Winter Ahead -- Sundays -- Nathan -- Love Finds a Home.
"Newly edited and revised"--Title page verso.
Keywords: Davis family (Fictitious characters : Oke) -- Fiction; Women pioneers -- Fiction; Christian fiction; Western stories; Love stories